Optimasi Aktivitas Antioksidan Peptida Aktif dari Ceker Ayam Melalui Hidrolisis Enzim Papain - Edy Susanto; Djalal Rosyidi; Lilik Eka Radiati; Subandi Subandi (Jurnal Ilmu dan Teknologi Hasil Ternak (JITEK), 2018)
The objective of this study was to optimization antioxidant activity of active peptides of chicken feet with papain hydrolysis. The research method was experimental design conducted using Factorial Completely Randomized Design. Treatments included papain concentration (control (0%) , 1%, 2% and 4%) and Incubation time (24 hours, 36 hours and 48 hours) were repeated four times. The variables observed were proximate analysis,microstructure, dissolved protein concentration and antioxidant activity. The results indicate that the treatment of papain concentration and incubation time variations in chicken feet protein extraction gave a differenceinfluence (P <0.05) to the concentration of solubility protein and antioxidant activity. The interaction of 3% papain concentration and 36 hours incubation time resulted in the highest antioxidant activity amount 55.10 ± 2.24 %. It could be concluded that chicken feet produced bioctive peptide compound that gave high antioxidant activity optimized by hydrolysis of papain enzymes thereby increasing their functional value.